# Answer to Question #16953 in Calculus for hsd

Question #16953

Which of the following explains how to obtain the graph of y=2+5(1+e^(−x)) from the graph of y=e(−x)?

(a) Vertically stretch the graph of y=e^(−x) by a factor of 5 and then shift this result up 2 units.

(b) Vertically stretch the graph of y=e^(−x) by a factor of 5 and then shift this result down 2 units.

(c) Vertically stretch the graph of y=e^(−x) by a factor of 5 and then shift this result up 7 units.

(d) Vertically stretch the graph of y=e^(−x) by a factor of 5 and then shift this result down 7 units.

(a) Vertically stretch the graph of y=e^(−x) by a factor of 5 and then shift this result up 2 units.

(b) Vertically stretch the graph of y=e^(−x) by a factor of 5 and then shift this result down 2 units.

(c) Vertically stretch the graph of y=e^(−x) by a factor of 5 and then shift this result up 7 units.

(d) Vertically stretch the graph of y=e^(−x) by a factor of 5 and then shift this result down 7 units.

Expert's answer

Note that y(x) = 7 + 5e^(-x), that for every x0 y(x0) is obtained from e^(-x0) by

stretching the graph by 5 and shifting UP (+7).

Answer. c).

stretching the graph by 5 and shifting UP (+7).

Answer. c).

## Comments

## Leave a comment